Buddha : a story of enlightenment - Chopra, Deepak (New York HarperCollins Publisher, 2007)
An novelized account of the life of the Buddha traces his spiritual journey while explaining how his experiences and teachings have changed the world and continue to influence every facet of life.
Age Group: Adult
Keywords: Biographical Fiction; Buddhism - Fiction; Buddhists -- India -- Biography -- Fiction; Guatama Buddha -- Fiction